The physiological role of carotenoids and their use in food technologies - A. D. Achmiz; E. V. Lisovaya; E. P. Viktorova; A. A. Skhalyakhov (Новые технологии, 2023)
Carotenoids are widely used and demanded as natural dyes in food technologies due to their biologically active properties. Due to antioxidant properties, carotenoids are widely used for the prevention and treatment of various human diseases, including oncological, cardiovascular, diabetes, etc. In addition, carotenoids are the main sources of vitamin A, which is not produced by the human body, but has a great influence on eye-sight, growth, development and reproductive function of the body. The purpose of the research is to analyze scientific and technical literature to determine the physiological function of carotenoids and the possibilities of their use in food technologies. Carotenoids enter the human body with food and their presence in sufficient quantities in the human diet ensures the normal functioning of the body. The issues of using lycopine and beta-carotene as food dyes and food additives in food technologies have been considered, as well as biologically active components when creating food products, including specialized, functional and personalized ones.The analysis of scientific information has shown that, due to their biological properties, carotenoids perform an important physiological function in a person’s life. The expansion of the area of their use determines the increase in the production of carotenoids and food using them. In accordance with this, studies in the field of improving existing technologies for obtaining carotenoids and expanding the raw material base are relevant, including the use of secondary resources of processing carotene -containing raw materials.